Using the Rice Husk Filtrate as Alternative Medium for Oxalic Acid Production Byaspergillus Niger - Ahmed Abed Faisal Al-Rikabi, Majid Kadhim Abboud Al-Shibli (Pakistan Journal of Medical & Health Sciences, 2022)
The aim of this study was to select cheaper and high yielding alternative medium, like rice husk filtrate, for oxalic acid production by A.niger fungus, in comparison to other culture media that have been used including, Potato Dextrose Agar (PDA), Sabouraud Dextrose Agar (SDA), and Sabouraud Dextrose Broth (SDB). The results showed that the highest percentage of oxalic acid production happens with rice husk filtrate medium, when its productivity was (12.02%), and reached (15.56 %), when rice husk filtrate was used as a solvent for (SDB) powder. It was followed by (SDB) medium, with a production rate of (5.06), then (SDA) with a production rate of (4.94), and (PDA) which gave the lowest production rate (3.67%) Keywords: Oxalic acid, A.niger, Rice Husk Filtrate medium